Sistem CRISPR/Cas9 in njegova uporaba v genetskem inženirstvu - Srpčič, Anja (Farmacevtski vestnik, 2023)
The CRISPR/Cas9 system is a recently discovered bacterial adaptive immune response against viruses and foreign DNA that enters a bacterial cell. The CRISPR/Cas9 system recognises and degrades foreign DNA after entering a bacterial cell. At the same time, the system incorporates part of the foreign DNA into its own genome, so that it remains as a “memory” of the foreign DNA, which enables rapid recognition and degradation in case of repeated infections. The essence of the system is the recognition of the foreign DNA by a complementary short sequence of RNA and the endonuclease Cas9, which recognise foreign DNA, bind and degrade it. with the discovery of this bacterial immune system, wide possibilities have appeared for its use in biotechnological purposes. In the last decade, methods have been developed for knocking out, knocking down and activating any gene in any organism. The CRISPR/Cas9 system enables fast, efficient and specific modification of the genome. In this review article, we present the mechanism of CRISPR/Cas9 immune response and the possibilities of its use in biotechnology and biomedical sciences.
Keywords: CRISPR/Cas9; Genetski inženiring; genetsko urejanje; genska terapija; Imunski odziv; izbijanje genov